2006
DOI: 10.1016/j.jtcvs.2005.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Extended donor criteria in lung transplantation: Impact on organ allocation

Abstract: Objective: Some reports have documented a higher early mortality with the use of extended criteria donors in lung transplantation. None have evaluated how outcomes compare with the use of these organs for single and bilateral transplantation or whether this practice results in a higher incidence of early bronchiolitis obliterans syndrome.Methods: We performed a retrospective review of case notes, intensive therapy unit database, and donor details. Between January 1, 2000, and December 31, 2004, 201 patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 19 publications
3
53
0
3
Order By: Relevance
“…There is a worldwide gap between the supply and demand for transplantable organs, and this gap is enlarging (19). However, another major issue is that the use of marginal donor lungs is associated with an increased incidence of primary graft dysfunction, with poor early and long-term outcomes in recipients of such suboptimal organs (3). Hence, transplant teams tend to be conservative in the selection of donor lungs (29).…”
mentioning
confidence: 99%
“…There is a worldwide gap between the supply and demand for transplantable organs, and this gap is enlarging (19). However, another major issue is that the use of marginal donor lungs is associated with an increased incidence of primary graft dysfunction, with poor early and long-term outcomes in recipients of such suboptimal organs (3). Hence, transplant teams tend to be conservative in the selection of donor lungs (29).…”
mentioning
confidence: 99%
“…Although the introduction of the Lung Allocation Score (LAS) (2) in May, 2005, has shortened the average time spent awaiting lung transplantation (3), potential recipients continue to die on the waitlist (4). To address the lung shortage, institutions have turned to extended-criteria donors (5,6) and donors after circulatory determination of death (7)(8)(9)(10)(11). Despite these strategies, a substantial gap remains between the supply of and demand for transplantable lungs.…”
mentioning
confidence: 99%
“…146 Many studies reported approximately 50 to 100 recipients of extended criteria lungs compared to approximately equal or larger numbers of recipients of standard lungs and found no significant differences in lung function, or short-or long-term survival up to 1 year following transplantation. [147][148][149][150][151][152] However, a number of similarly sized studies suggested caution in proceeding with transplantation using extended criteria donor lungs based on increased rates of early or late mortality, 153,154 increased primary graft dysfunction either in the postoperative period or after 1 or more years after transplant, 153,155 longer ICU courses, or prolonged hospital stays. 155 Interpretation of these studies is generally difficult because of the moderately small numbers of patients with widely varying characteristics and multiple paths to qualification as an extended criteria donor.…”
Section: Extended Criteria Donationmentioning
confidence: 99%